Upaya Kepala Sekolah Dalam Meningkatkan Kedisiplinan Guru Di SD Negeri 9 Labuhanhaji - Hayatul Masruri (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2022)
Each school principal has its own efforts to improve discipline of teachers in their schools, the efforts that have been designed will be implemented to teachers who have problems with discipline. Formulation of the problem in this study is how the principal’s efforts in improve teacher discipline at SD Negeri 9 Labuhanhaji and what are the obstacles faced by principals in an effort to improve teacher discipline in elementary schools Land 9 Labuhanhaji. This study aims to describe the efforts of principals in improving teacher discipline and the obstacles faced principals in an effort to improve teacher discipline at SD Negeri 9 Labuhanhaji. The approach in this research is qualitative with the type of descriptive research. The subjects of this study consisted of 1 principal and 7 teachers at SD Negeri 9 Labuhanhaji. Data collection techniques are carried out by means of observation and interviews, and analyzed by data reduction, presentation of data and drawing conclusions. The result of this study show that the principal’s efforts in improving teacher discipline are make rules, direct teachers to implement the rules, give motivation at every opportunity and the provision of sanctions in the form of warnings, advice and warnings to undisciplined teachers. Conclusions from this research is an effort that is applied by the principal to the three forms of discipline have a relatonship, namely making regulations and providing sanctions if non-compliance with regulations, efforts and sanctions are carried out consistently against teacher. The obstacle faced by the principal is not being able to supervise teachers directly if you have an outside interest and the level is not maximized discipline of the teacher, so to minimaze these obstacles the principal ask the treasurer or the picket tacher for help to supervise and the head schools try to enforce regulations, increase cooperation and always create a good relationship with the teacher council.